Penerapan Model Team Games Tournament (TGT) untuk Meningktkan Minat dan Hasil Belajar Bahasa Arab Peserta Didik Kelas XI MIA I MA Alkhairaat Kalangkangan - Rezki Awalia; Sitti Aisyah Chalik; Azizul Hakim (Universitas Islam Negeri Alauddin, 2025)
This study aims to explore the implementation process of the Team games Tournament (TGT) model to enhance the interest and learning outcomes in Arabic language for students in class XI MIA I at MA Alkhairaat Kalangkangan. The study employs a mixed method approach, combining qualitative and quantitative methods, using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which includes planning, implementation, observation, and reflection across two cycles. Data were collected through learning interest questionnaires, achievement tests, and classroom observation. The results show an increase in learning interest from 58.04% in cycle I to 70.4% in cycle II. Meanwhile, learning outcomes improved from 63.43% in cycle I to 77.42% in cycle II, with an 88.57% completion rate. The TGT model proved effective in creating an engaging learning environment, stimulating motivation, and encouraging active student participation in Arabic language learning.